Effect on Pregnancy Outcome of Hysteroscopy Combined with Chronic Endometritis Screening before the Next Frozen-Thawed Embryo Transfer in Patients with Previous Failed Transfer Cycle - Tianji Liao; Lijun Lin; Li Xiao; Wei Huang (Clinical and Experimental Obstetrics & Gynecology)
Background: Implantation failure, especially recurrent implantation failure (RIF), causes considerable distress in patients who undergo assisted reproductive techniques (ART). Mild pathologies inside the uterine cavity and disturbance of the uterine environment can decrease endometrial receptivity and cause implantation failure. To address this, hysteroscopy combined with endometrial pathological diagnosis has become more widespread. However, the specific time at which to perform the hysteroscopy remains controversial in the clinical practice of ART. Methods: This case-control studies enrolled a total of 1876 in-vitro fertilization embryo transfer (IVF-ET) or intracytoplasmic sperm injection embryo transfer (ICSI-ET) patients with a history of failed implantation were included in this study. From October 2019 to December 2022, these patients underwent office hysteroscopy and subsequent endometrial biopsy for CD138 immunohistochemistry to detect chronic endometritis (CE) in the Department of Reproductive Medicine, West China Second University Hospital, Sichuan University. Endometrial polys (EP) were removed during surgery, and for patients diagnosed with CE, oral doxycycline was taken for two consecutive weeks before the next frozen embryo transfer (FET). Patient demographic characteristics and pregnancy outcomes were reviewed and analyzed by logistic regression to evaluate outcomes. Results: Patients were divided into four groups according to hysteroscopy findings and pathological diagnosis: CE only, CE plus EP, EP only, and neither CE or EP. The biochemical pregnancy (p = 0.009), clinical pregnancy (p = 0.014), and live birth (p = 0.011) rates after the following FET cycle were significantly different between the four groups. Pregnancy outcomes for the CE plus EP group were better than for the other three groups. Multivariate logistic regression analysis revealed that the probability of live birth was significantly related to the mother’s age, the controlled ovarian stimulation (COS) protocol, the number of times with failed embryo transfer (ET) cycle, endometrial histology findings, the interval time between hysteroscopy and FET, the endometrial thickness on the day of embryo transfer, and the number and type of embryos transferred (p < 0.05). Conclusions: Office hysteroscopy combined with diagnosis of endometrial pathology is a valuable approach for women with a history of implantation failure. This approach is not limited to RIF patients, and results in an increased pregnancy rate and shorter time to live birth in ART.